Disulfide bond formation and redox regulation in the Golgi apparatus. Issue 22 (4th November 2022) - Reznik, Nava; Fass, Deborah
Abstract : Formation of disulfide bonds in secreted and cell‐surface proteins involves numerous enzymes and chaperones abundant in the endoplasmic reticulum (ER), the first and main site for disulfide bonding in the secretory pathway. Although the Golgi apparatus is the major station after the ER, little is known about thiol‐based redox activity in this compartment. QSOX1 and its paralog QSOX2 are the only known Golgi‐resident enzymes catalyzing disulfide bonding. The localization of disulfide catalysts in an organelle downstream of the ER in the secretory pathway has long been puzzling. Recently, it has emerged that QSOX1 regulates particular glycosyltransferases, thereby influencing a central activity of the Golgi. Surprisingly, a few important disulfide‐mediated multimerization events occurring in the Golgi were found to be independent of QSOX1. These multimerization events depend, however, on the low pH of the Golgi lumen and secretory granules. We compare and contrast disulfide‐mediated multimerization in the ER vs . the Golgi to illustrate the variety of mechanisms controlling covalent supramolecular assembly of secreted proteins. Abstract : Catalyzed disulfide bond formation in the Golgi apparatus is more limited than in the endoplasmic reticulum and appears to have a regulatory function. The Golgi disulfide catalyst QSOX1 oxidizes glycosyltransferases and thereby influences sialic acid addition to glycans. QSOX1 is not required for the major disulfide‐mediated protein complex assembly processes that occur in the Golgi.